2014
DOI: 10.1179/1351000214y.0000000117
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of kaempferol, a flavonoid, on oxidative stress in streptozotocin-induced diabetic rats

Abstract: Objective: The aim of the present study was to evaluate the protective effect of kaempferol against oxidative stress in streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes was induced in male, adult albino rats of the Wistar strain, by intraperitoneal administration of STZ (40 mg/kg body weight (BW)). Kaempferol (100 mg/kg BW) or glibenclamide (600 μg/kg BW) was administered orally once daily for 45 days to normal and STZ-induced diabetic rats. Results: The STZ-induced diabetic rats showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 51 publications
(44 reference statements)
7
98
0
3
Order By: Relevance
“…Increased MDA (Table ) in the liver of diabetic rats confirm oxidative damage. Fractions A (quercetin) and B (kaempferol) reversed the alterations in antioxidant enzymes (SOD and CAT), glutathione and lipid peroxidation product (MDA) suggesting antioxidant activity as demonstrated in studies in different experimental models (Aherne & O'Brien, ; Al‐Numair et al, ; Gupta, Vikram, Tripathi, Ramarao, & Jena, ; Kaindl, Eyberg, Rohr‐udilova, Heinzle, & Marian, ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Increased MDA (Table ) in the liver of diabetic rats confirm oxidative damage. Fractions A (quercetin) and B (kaempferol) reversed the alterations in antioxidant enzymes (SOD and CAT), glutathione and lipid peroxidation product (MDA) suggesting antioxidant activity as demonstrated in studies in different experimental models (Aherne & O'Brien, ; Al‐Numair et al, ; Gupta, Vikram, Tripathi, Ramarao, & Jena, ; Kaindl, Eyberg, Rohr‐udilova, Heinzle, & Marian, ).…”
Section: Resultsmentioning
confidence: 81%
“…Kaempferol and quercetin have been reported to improve the lipid profile of diabetic rats (Al‐Numair, Chandramohan, Veeramani, & Alsaif, ; Yang & Kang, ). Consistent with these studies, the isolated compounds significanlty lowered elevated TC, TAG and LDLc, and raised HDLc in the serum of alloxan‐induced diabetic rats when compared to the control rats (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study results are in par with previous studies, where reduced MDA levels with increased SOD, CAT, and GPx activity levels were observed in KF‐treated ISO‐induced cardiac toxicity in rats (Suchal et al, ). Recently, a few other studies showed that KF treatment reduced the LPO and bought back antioxidant enzymes like SOD, CAT, GPx, and GST in liver, kidney, and heart of diabetic rats (Al‐Numair, Chandramohan, Veeramani, & Alsaif, ) and ISO‐induced myocardial injury rats (Zhou, Ren et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin ameliorates insulin resistance and inhibits alpha-amylase and alpha-glucosidase enzyme activities [35, 36]. Similarly, kaempferol is another typical dietary flavonoid that was shown to have many beneficial activities including anti-diabetic, antioxidant, and anti-inflammatory through promoting functions of pancreatic β-cell [37]. It was also shown to have positive effect on lipid metabolism, stimulate insulin-dependent glucose uptake and improve insulin resistance [38].…”
Section: Discussionmentioning
confidence: 99%